(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
In the 16th century Ovid’s Metamorphoses was the object of several translations and rewritings, either of single books or the whole poem; therefore, the great poems of Boiardo and Ariosto become the point of reference for proposing the Latin poem so as to match the expectations of the readers of the Italian Renaissance. This paper will focus on the preface of Lodovico Dolce’s Trasformationi, published for the first time by Giolito in 1553 in Venice, in order to show the recovery of elements related to the almost contemporary chivalric romances. Dolce imitates Ariosto but, as is to be expected, includes some variations in the text. Moreover, the essay aims to shed light on some differences in the proemio through a comparison between the first edition printed in 1553 and another edition, published by Francesco Sansovino in 1568 in Venice.